The link of feast-phase dissolved oxygen (DO) with substrate competition and microbial selection in PHA production. (1st April 2017) - Wang, Xiaofei; Oehmen, Adrian; Freitas, Elisabete B.; Carvalho, Gilda; Reis, Maria A.M.
Abstract: Polyhydroxyalkanoates (PHAs) are biobased and biodegradable polyesters with the potential to replace conventional plastics. Aeration requires large amounts of energy in PHA production by mixed microbial cultures (MMCs), particularly during the feast phase due to substrate uptake. The objective of this study was to investigate the impact of DO concentrations on microbial selection, substrate competition and PHA production performance by MMCs. This represents the first study investigating DO impact on PHA production while feeding the multiple volatile fatty acids (VFAs) typically encountered in real fermented feedstocks, as well as the substrate preferences at different DO levels. Efficient microbial cultures were enriched under both high (3.47 ± 1.12 mg/L) and low (0.86 ± 0.50 mg/L) DO conditions in the feast phase containing mostly the same populations but with different relative abundance. The most abundant microorganisms in the two MMCs were Plasticicumulans, Zoogloea, Paracoccus, and Flavobacterium. Butyrate and valerate were found to be the preferred substrates as compared to acetate and propionate regardless of DO concentrations. In the accumulation step, the PHA storage capacity and yield were less affected by the change of DO levels when applying the culture selected under low DO in the feast phase (PHA storage capacity >60% and yield > 0.9 Cmol PHA/Cmol VFA). A high DO level is required for maximal PHA accumulation rates with the four VFAs (acetate, propionate, butyrate and valerate) present, due to the lower specific uptake rates of acetate and propionate under low DO conditions. However, butyrate and valerate specific uptake rates were less impacted by DO levels and hence low DO for PHA accumulation may be effective when feed is composed of these substrates only. Graphical abstract: Highlights: Efficient PHA storage cultures were selected at both high and low DO in feast phase. Butyrate and valerate were preferred as substrates regardless of DO concentration. High DO is essential for PHA accumulation at its maximal rates. Low DO would be applicable for PHA accumulation if feeding butyrate and valerate.